Practice of Subsistence Farming System in Bhojpur, Eastern Hills of Nepal - Rai, Dhyanendra Bahadur (Tribhuvan University Journal, 2017)
Nepalese hill agriculture is a subsistence type of farming system. Development of agriculture follows different trajectories as an outcome of both biophysical and cultural factors for production while culture determines the strategy and the extent of the technological inputs. The main objective of this study is to assess agricultural practice and calculate cost and benefit of crop production in the study area. This study is based on case study of Bhojpur VDC of Eastern hill of Nepal. Data were collected from household survey, key informant interview and field observation. Finding indicates that the crop-livestock combination is the main basis of livelihood of the people in the study area. Land and labor are the main components of the farming system. Maize, potato and millet are traditional crops. Likewise, potato and maize are the most important crops of high zone area. It is cultivated both in irrigated and non-irrigated fields. Paddy is the most important crop in middle zone. Maize, millet and potato are other important crops of this zone. High zone has benefit only in potato production and this zone has no paddy production due to cold climate and no irrigation facility. This zone is deficit in maize and millet production. Middle zone is in benefit only for millet production. Low zone is highly surplus situation in potato, maize and millet but deficit in paddy production. In general, Lower zone is the most suitable area for crop production compared with higher zone areas. However, paddy production is deficit even in lowland area. Cost and benefit analysis indicates that there is low economic return for the farmers in the study area.